Laboratory Investigation on Salinity Tolerance to Barbodes Gonionotus (Bleeker) (Progressive Agriculture, 2013)
Salinity tolerance to Thai silver barb, Barbodes gonionotus was investigated under laboratory conditions using common salt (NaCl) and sea water. With a view to determine the median lethal concentrations (LC50 values), the fish were exposed to various concentrations of the salt and sea water for a period of 96. Common salt up to a concentration of 12 ppt and sea water up to a concentration of 10 ppt did not cause mortality to the experimental fish. The LC50 values for 6h, 12h, 24h, 48h, 72h, and 96 hexposure times were 17.91 ppt, 16.91 ppt, 15.35 ppt, 14.51 ppt and 13.92 ppt common salt, respectively. During experiment action with sea water, the LC50 values obtained were 15.02 ppt, 14.18 ppt, 13.48 ppt, 12.61 ppt, 12.35 ppt and 12.25 ppt for 6 h, 12 h, 24 h, 48 h, 72 h and 96 h exposure times, respectively, On the other hand, pre-exposure acclimation in modifying the acute lethal toxicity of the salt showed, a concentration of 18 ppt salt killed all the fish within 4 days, indicating that gradual increases in salinity increases the salt tolerance of B. gonionotus.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16871 Progress. Agric. 20(1 & 2): 193 200, 2009